Uptake Patterns of Glycine, Ammonium, and Nitrate Differ Among Four Common Tree Species of Northeast China - Zhu, Feifei; Dai, Luming; Hobbie, Erik A.; Koba, Keisuke; Liu, Xueyan; Gurmesa, Geshere A.; Huang, Shaonan; Li, Shanlong; Li, Yinghua; Han, Shijie; Fang, Yunting (Frontiers in Plant Science, 2019)
Fundamental questions of how plant species within secondary forests and plantations in northeast China partition limited nitrogen (N) resource remain unclear. Here we conducted a 15N tracer greenhouse study to determine glycine, ammonium, and nitrate uptake by the seedlings of two coniferous species, Pinus koraiensis (Pinus) and Larix keampferi (Larix), and two broadleaf species, Quercus mongolica (Quercus) and Juglans mandshurica (Juglans), that are common in natural secondary forests in northeast China. Glycine contributed 43% to total N uptake of Pinus, but only 20, 11, and 21% to N uptake by Larix, Quercus, and Juglans, respectively (whole plant), whereas nitrate uptake was 24, 74, 88, and 68% of total uptake for these four species, respectively. Retention of glycine carbon versus nitrogen in Pinus roots indicated that 36% of glycine uptake was retained intact. Nitrate was preferentially used by Larix, Quercus, and Juglans, with nitrate uptake constituting 68∼88% of total N use by these three species. These results demonstrated that these dominant tree species in secondary forests in northeast China partitioned limited N resource by varying uptake of glycine, ammonium and nitrate, with all species, except Pinus, using nitrate that are most abundant within these soils. Such N use pattern may also provide potential underlying mechanisms for the higher retention of deposited nitrate than ammonium into aboveground biomass in these secondary forests.